Education as Empowerment: Twins in Search of an Alternative Education - Majumdar, Swapan (JOURNAL OF INDIAN EDUCATION, 2009)
Of the multi-faceted activities of Rabindranath Tagore, education had been the corner-stone. He was not only a visionary and philosopher of education, he was at the same time an ardent activist for the cause of education. He stands unique also as a writer on education which extends from creative to critical constructive writings on the subject. On the other hand, he even sacrificed personal family property to give his ideas a tangible form.Tagore’s first effort in setting up a family school started at Sialadh in 1898. In the same year, in keeping with the stipulation of the Trust Deed willed by his father Devendranath Tagore. Tagore’s nephew Balendranath started a Brahmacharyasrama in Santiniketan. It was a very shortlived enterprise. In 1901, Tagore moved to Santiniketan and revived the school which passing through a process of reforms was made into an eastern university, Visva-Bharati, in 1921. In 1924, he added a new school, Siksha-Satra for the depraved section at Sriniketan, among the cluster of faculties. Tagore was constantly engaged in experimenting and improving the pedagogic quality and system practised in his institution. His other worry was to collect adequate finance to sustain it. Many fellow travellers throughout the world came forward to help him in different ways. It was truly an essay negotiating with western modernism on the one hand, and colonial education system, on the other. For Tagore, education did not consist in achievements alone. His ideal was to help create a complete man by making open choices and opportunities before the students and thereby letting them develop their latent talents. Generation of Atmasakti or self-reliance for him was not conditioned by anti-colonial excitement, it was the result of all out self-disciplining in life.Through Visva-Bharati Tagore was also trying to negotiate the East-West relations seen from the vantage of the East. That too was aimed at a reconciliation of the best features of the two cultures. In the process Tagore had also been trying to create alternative spaces for cultures of creativity – the ultimate ideal of education for Tagore. The second half of the paper deals with the theme of empowerment as approached by two great minds of our times – Tagore and Gandhi. Their approach routes may be apparently different, they might also have differences in opinions and positions, yet the innermost truth they had been seeking in their educational enterprises underlines the amity of visions.